Political Economy of Data Nationalism - Kaushambi Bagchi; Sashank Kapilavai (International Telecommunications Society (ITS), 2018)
Dominant narratives on data localization stress on the self-defeating nature of data localization measures in enhancing privacy and security, and stress on potential inefficiencies it imposes on trade and the significant economic costs that follow. However, the literature, in as much as its argument is based on the premise of free trade and competition, do not widely acknowledge the nature of digital economy, which tends towards market concentration and presence of 'superstar' firms, and the active role of the state and global power configurations, in either engaging with negotiating trade agreements, or actively promoting its domestic economy and most importantly, configuring the nature of its sovereignty in a fast changing and uncharted realm of the cyberspace This paper attempts to focus on the role of the State, particularly the interplay of State Capacity, defined in terms of the ability of states to divert revenues for enhancing welfare, and enabling legal infrastructure that promotes productive capacities of its economy, and data localization laws that have been triggered by nations across, in their attempts to claim sovereignty in an erstwhile border-free cyberspace. Conjecturing on the interplay of State Capacity and Data localization laws leads us to believe that the outcomes of data localization laws cannot, in any straightforward way, be harmful. State capacity, we conjecture is a crucial variable which at least, in part, determines the outcomes of data localization measures.
Keywords: 330